Kepribadian Islami dan Kualitas Kepemimpinan - Ramon Ananda Paryontri (Unisia, 2015)
The aim of writingthis paper is to discuss the effect of Islamic personality towardleadership quality. Individual that has Islamic personality will give effect on the leadershipquality especially in the way he manages the members or the group. This paper will discuss indetail the scope of the Islamic personality, factors that affect the formation of the Islamicpersonality, personality aspects of islam and its effect on the quality of the leadership of theIslamic personality of a person. Good personality has been described in the Quran andexemplified by the Prophet Muhammad to form a good personality. Islamic personality is anideal illustration for moslem individuals who can run with good religion. The Islamicpersonality ultimately shapes the powerful character and ultimately affects the quality ofleadership of the individual him/herself. The quality of individual leadership to the organizationhe leads can be seen from the social maturity, emotional maturity, good interpersonalrelationship, ability to solve problems, and accuracy in making decisions. Basically, the qualityof leadership is strongly influenced by a good personality and Islamic personality is the key forindividuals in developing the quality of life, including in terms of leadership.